PENGARUH PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA AKUNTANSI UNIVERSITAS ISLAM MALANG - Moh. Haris; Noor Shodiq Askandar; Abdul Wahid Mahsuni (Universitas Islam Malang, 2020)
ABSTRACT This research was conducted to analyze the effect of investment decisions, funding decisions, ownership structure, and dividend policy on company value in LQ-45 companies listed on the Indonesia Stock Exchange (IDX) 2015-2017 period. The sample in the study was taken using a purposive sampling method. The population in this study were LQ-45 companies listed on the Indonesia stock exchange (BEI) for the 2015-2017 period, so that there were 45 companies in the study population. As for those selected according to the specified sample criteria from 3 years (2015-2017) the observation period is 30 companies. Data were analyzed using multiple linear regression analysis with Shoftware SPSS 22 For Windows. Based on the results of simultaneous hypothesis testing shows that investment decisions (PER), funding decisions (DER), ownership structure (KMM) and dividend policy (DPR) significantly influence the value of the company (PBV). The results of the partial hypothesis test show that investment decisions (PER) and ownership structures (KMM) have no effect while the funding decisions (DER) and dividend policies(DPR) significantly influence the LQ-45 companie value (PBV) listed on the Indonesia Stock Exchange (IDX) for the 2015-2017 period. Keywords: Corporate value, investment decisions, funding decisions, ownership structure, dividend policy.